Indonesian folktales: feminism and the query of femaleness - Sulasih Nurhayati (University of Muhammadiyah Purwokerto, 2019)
This paper aims to study about the query of femaleness in Indonesian folktales from the feminism approach. It is taken into account due to women’s subordination that allegedly implies the negation of femaleness. In particular, the perpetual story of Malin Kundang represents that owing to her weakness, a woman is a subordinate creature. It happens when Malin Kundang denies the appearance of her mother after a series of successes he makes. Another popular story, Sangkuriang, even depicts that due to her beauty, a woman is an object of sex. It is seen when Sangkuriang proposes Dayang Sumbi to be his wife because of his inability of recognising her as his mother after some year banishment. The subordination eventually drives the two women to struggle against it in order to defend their dignity. The mother of Malin Kundang spells him to be a stone and Dayang Sumbi overtly refuses Sangkuriang’s proposal. Their struggles are of course valued of the morality for wider public, too. Despite this, the tales remain a query of women’s existence, particularly that of femaleness. The truth that a woman is biologically and socially the mother of man is denied in order to sustain men’s superiority. By biologically it means that a woman is the undenied creature for her gifted power of childbirthing. It then socially gives her more power to sustain the generations and the social relationships. Furthermore, it is pivotal to investigate the feminist critical ideas about the essence of femaleness in the Indonesian folktales.